The Effect of Corporate Risk-taking on Company Performance in View of the Firm Life Cycle - Rahayu, Wulandari Tri; Yusra, Irdha (Universitas Negeri Padang, 2024)
Examining the impact of Corporate Risk-Taking (CRT) on business performance over the firm life cycle is the primary objective of this research. Participating manufacturing enterprises from the 2020–2022 timeframe on the Indonesia Stock Exchange made up the study's population. Similarly, the research sample was selected by a purposive sampling procedure. We used 356 pieces of observational data from 137 different firms in our sample. The multiple linear approach, implemented in SPSS Statistics 24, was used for the study. First, CRT as measured by the standard deviation of ROA has a positive impact on performance. Second, CRT as measured by the standard deviation of stock returns has no effect on performance. Third, CRT as measured by the standard deviation of ROA has a negative impact on performance during the introduction stage but a positive impact during the maturity stage. Fourth, CRT as measured by the standard deviation of stock returns has no effect on performance throughout all lifetime stages of a company